The Effect of Graft Harvest and Skin Incision Angle on Sensory Disturbance in ACL Reconstruction With Semitendinosus-Gracilis Tendon Graft: A Randomized Controlled Trial and Cadaveric Study. Issue 9 (15th September 2020) - Leiter, Jeffrey; Peeler, Jason; McRae, Sheila; Wiens, Scott; Hammond, Allan; Froese, Warren; MacDonald, Peter
Background: Injury to the inferior branch of the saphenous nerve (IBSN) and the subsequent loss of skin sensation after anterior cruciate ligament (ACL) reconstruction are common. The literature suggests that the incision angle may affect the incidence and area of loss of skin sensation. Purpose: To determine whether there is a difference in the incidence and area of altered sensory loss on the tibia between vertical (VI) and oblique (OI) incisions for semitendinosus-gracilis tendon graft harvest during ACL reconstruction. The cadaveric component was designed to determine whether there is a "safe zone" for incision by identifying the location and number of branches of the IBSN. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: Patients (n = 37) were randomized to receive either VI or OI. Incidence and area of altered skin sensation were documented during at least 1 postoperative visit. In addition, 18 cadaveric knees were dissected. Results: The presence or absence of hypoesthesia did not differ between groups postoperatively. Although no statistical differences between groups were seen in the total area of perceived altered skin sensation at 3 ( P = .57), 6 ( P = .08), 12 ( P = .65), and 24 months ( P = .27), data demonstrated a trend toward VI participants having a larger area of hypoesthesia at every time point. Among the 18 cadaveric specimens, 4 variations in the distribution of IBSN were noted: 18 (100%) had 1 branch, 14 (78%) had 2 branches, 6 (33%) had 3 branches, and 1 (6%) had 4 branches. No safe zone for incision could be identified. Conclusion: No difference was found between a vertical and an oblique incision with respect to incidence or area of sensory loss. Furthermore, it was not possible to identify a safe zone that would prevent transection of all nerves branches of the IBSN based on the cadaveric component of this study.